If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + -5q = 20 Solving 2p + -5q = 20 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '5q' to each side of the equation. 2p + -5q + 5q = 20 + 5q Combine like terms: -5q + 5q = 0 2p + 0 = 20 + 5q 2p = 20 + 5q Divide each side by '2'. p = 10 + 2.5q Simplifying p = 10 + 2.5q
| 14*3+2= | | 8+23x= | | x^2+5x+8=x^2+3x-7 | | 2x+9y-7z=-16 | | 18+3+2x=306 | | 6a^2+31a+5= | | 9+6(x-3)=7-5(x-9) | | 3(6+5)= | | 32+x^2=12x | | 12x-8=10-3x | | 2x^3+133=0 | | -4p+4=p+7 | | 2x^3+125=8 | | x^3+5x^2-10x-40=12x+16 | | 4x+43-5x=3-7x+4 | | 2(1+5x)=9(x-1) | | -3(-3+7x)=10-21.5x | | 2x+2-4=3x-17 | | 3t-3=17-t | | .72=.03x | | (x^2)+5x+8=(x^2)+3x-7 | | .23y=1840 | | (4x-5x-3)(1+2x^2)= | | 2.2x+5=1.2-4 | | 3x+6-8=4x-23 | | 0=-44 | | 185=-5(3+8n) | | Y=.75x+1.67 | | 8-23x= | | c=1388x+24963 | | -5+3=28 | | -89=5(7b+4)-4 |